2014
DOI: 10.1021/jp4108766
|View full text |Cite
|
Sign up to set email alerts
|

H2O/D2O Exchange on SnO2 Materials in the Presence of CO: Operando Spectroscopic and Electric Resistance Measurements

Abstract: Water isotope exchange in the presence of CO on two undoped tin dioxides has been studied using modulation excitation diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and resistance measurements at 300 °C. Our results reveal that the material synthesized from tin tetrachloride (SnO 2 Cl) manifests higher affinity to chemisorbed water than that made from tin hydroxide acetate (SnO 2 Ac). The latter was shown to exhibit a strong correlation between the evolution of surface OH groups (bridging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 64 publications
0
17
1
Order By: Relevance
“…Some studies have been reported focusing mainly on chlorides, showing detrimental effects in terms of surface area 82 and modifications in the reaction mechanism of SnO 2 with CO, the latter slightly reducing (by a factor of 2) the response amplitude to CO for samples prepared from tin tetrachloride with respect to that for samples prepared from tin hydroxide acetate. 83 Nevertheless, none of these previous studies show effects comparable to those observed in the present work, in which the whole set of morphological, structural, electrical, and gas-sensing measurements suggests the capability of K to decreasing the response to gases by orders of magnitude, despite a clear opposite trend in the material microstructure.…”
Section: Resultscontrasting
confidence: 68%
“…Some studies have been reported focusing mainly on chlorides, showing detrimental effects in terms of surface area 82 and modifications in the reaction mechanism of SnO 2 with CO, the latter slightly reducing (by a factor of 2) the response amplitude to CO for samples prepared from tin tetrachloride with respect to that for samples prepared from tin hydroxide acetate. 83 Nevertheless, none of these previous studies show effects comparable to those observed in the present work, in which the whole set of morphological, structural, electrical, and gas-sensing measurements suggests the capability of K to decreasing the response to gases by orders of magnitude, despite a clear opposite trend in the material microstructure.…”
Section: Resultscontrasting
confidence: 68%
“…These spectroscopic techniques were developed from an in situ to a powerful operando technique for gas sensor research within a few years. [ 18,56,79,80‐81 ] For example, Chen et al . employed the in situ diffuse reflectance infrared Fourier transform spectroscopy ( in situ DRIFTS) technique…”
Section: Characterization Of Oxygen Defects In Nanostructured Metal Oxidesmentioning
confidence: 99%
“…(a) Time‐resolved DRIFTS spectra of the porous ZnO nanoflakes after adsorption of 9800 ppm NO 2 /He at room temperature for different time. [ 81 ] Time‐resolved DRIFTS spectra of (b) SnO 2 NCs, and (c) SnO 2− x (1 : 2.5) NCs. [ 22 ] (d) Schematic illustration of proposed mechanism for the sensing of ethanol gas during the operando operating.…”
Section: Characterization Of Oxygen Defects In Nanostructured Metal Oxidesmentioning
confidence: 99%
“…Using a combination of time resolved DRIFTS and impedance measurements, conductivity changes in ZSM-5-based catalysts during the selective catalytic reduction of nitrogen oxides were successfully assigned to a certain adsorbed NH 3 species, by comparing the time constants of the electrical response and the different adsorbed NH 3 species [ 39 ]. Other approaches using time-resolved methods are Modulation Excitation Spectroscopy (MES) [ 70 , 72 , 73 , 74 ], Steady State Isotopic Transient Kinetic Analysis (SSITKA) [ 68 , 75 ] and the evaluation of time-resolved data by Multivariate Curve Resolution (MCR) [ 76 , 77 ]. These rather sophisticated approaches are applied by various authors to study catalysts, but today there is just a small number of articles dedicated to the investigation of gas sensing materials [ 28 , 39 , 73 , 78 ].…”
Section: Identifying Active and Inactive Speciesmentioning
confidence: 99%
“…Other approaches using time-resolved methods are Modulation Excitation Spectroscopy (MES) [ 70 , 72 , 73 , 74 ], Steady State Isotopic Transient Kinetic Analysis (SSITKA) [ 68 , 75 ] and the evaluation of time-resolved data by Multivariate Curve Resolution (MCR) [ 76 , 77 ]. These rather sophisticated approaches are applied by various authors to study catalysts, but today there is just a small number of articles dedicated to the investigation of gas sensing materials [ 28 , 39 , 73 , 78 ]. A good example is the investigation of the NO 2 detection of In 2 O 3 , using MCR to analyze time resolved DRIFT spectra [ 28 ].…”
Section: Identifying Active and Inactive Speciesmentioning
confidence: 99%